Воющие псы одиночества: роман / Александра Маринина - Маринина Александра Борисовна (Эксмо, 2004)
Экземпляры: ф. 1 (20110315) / Инвентарный номер: 96942 / Цена: 100.00 / Авт.знак: М 26 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6